Marketing Strategy of MSMEs During the COVID-19 Pandemic Era for Catering Entrepreneurs - Putra, Chinatha Erwin Sandika; Kaimudin, Muhamad Sulsamar; Purwanto, R. Desardi; Adyatma, Satria; Rahmawati, Siti (Interdisciplinary Social Studies, 2022)
Many MSMEs have gone out of business as a result of restrictions on community activities during the pandemic, thus affecting income and decreasing business turnover. However, from several business sectors, the food and beverage industry is quite able to withstand the pandemic. With digital marketing or online sales, business actors take advantage of these opportunities to reduce the impact of the COVID-19 pandemic in selling food catering businesses. This study aimed to find out the MSMEs Marketing Strategy carried out by catering entrepreneurs named Mrs. Endah and Mrs. Yanti. The approaches used in this study are the literature review approach, journal documentation, and interviews. In this study, the literature review and journals used are the theories that are the basis for the research. Marketing strategies that can be done include using digital advertising media such as Instagram, Facebook, and Youtube, or using  other market places. This is done because customers do not have to meet and or gather directly at food stalls but can use delivery services. Thus, the net profit of catering business owners is expected to increase again.